ENGAGING LEARNERS WITH EVERYDAY ENGLISH ON TIKTOK: TEACHING STRATEGIES FROM @KADANG.SOKINGGRIS - Brillian Nugraha; Achmad Hilal Madjdi; Fitri Budi Suryani (Universitas Muhammadiyah Makassar, 2026)
This study seeks to analyze the teaching strategies that were found in English learning videos that are published on TikTok using account @kadang.sokinggris as the primary source. In the second phase, 25 videos were selected using purposive sampling methods. The videos were selected using multiple viewing, descriptive note taking and thematic coding. The aims of the study were (1) to identify the types of teaching strategies used, (2) to analyze how the teaching strategies were used in the videos, and (3) to identify the distinct characteristics of the teaching strategies used. This analysis leads to identifying four main groups of strategies. Direct instruction, on-screen text, humor and repetition are shown through multimodal means which combine verbal and non-verbal elements such as gesture, gaze, intonation and text on screen. The three parts of the overall approach taken by the videos' creators include personal humor, an adaptation of colloquial phrases to culture and audience participation. This multimodal approach allows for the more interactional, contextualized, and effective learning of English in the informal digital environment. This study seeks to contribute to the growing learning of online language pedagogy and to reveal the educational potential of short-form video in particular. The study also has pedagogical implications for English teachers and content creators on how to create social media material that is more linguistically relevant and culturally interesting.